(untitled) (Revista da EGN, 2023)
This paper is about three elements: inter-agency cooperation simulations with security and defense practitioners as actors; policy diffusion as a way of innovative and incremental gains using practices and the observation of behaviors; and, agent-based modelling as a tool to enhance performance, observing tendencies and acquiring more visibility of the processes and practices imbibed. For this, the first part of the paper is focused on the uses of the literature that expresses decision making process behaviors as a fundamental part of the institutionalization process in terms of cooperation. Adaptive institutionalization is the core element of this approach; in which we believe policy diffusion can derive progressively and in an incremental way. Secondly, we are going to present the inter-agency simulation cases we are working with as part of an inter-institutional effort; researching on those ties and proposing new forms of arrangements and possibilities of increasing dynamics efficiency in the sector, observing both the cases and the exercises chosen in agent-based modelling (ABM).